Comparative analysis of the physical and mechanical properties of kraft paper and watercolor paper - Li, Anling; Shi, Yameng; Zhang, Jiaqi; Zhang, Yong (Maderas. Ciencia y Tecnología, 2021)
In order to study the feasibility of kraft paper as watercolor paper, the wetting properties, mechanical properties and friction properties of kraft paper and watercolor paper were compared before and after aging. Aging test was carried out on kraft paper and watercolor paper by aging chamber, the wetting properties of distilled water and three watercolor solutions before and after aging of kraft paper and watercolor paper were compared, tensile tear test of paper on tensile testing machine, the fracture changes of paper were analyzed by scanning electron microscope, the friction tester performs the paper friction test. The results show that both kinds of paper are amorphous, watercolor paper was showed hydrophobicity before and after aging, contact angle was maintained at about 119,09° ± 5° in four different solutions, unaged kraft paper exhibited hydrophilicity, the aged kraft paper showed hydrophobicity with a contact angle of 92,52° ± 1°，the aged kraft paper shows better performance in both tensile and tearing aspects and tensile strength is 20 MPa higher than watercolor paper, surface roughness of kraft paper is higher than watercolor paper. The experiment is helpful for the market to consider whether the cheaper kraft paper replaces the more expensive watercolor paper in some aspects and provides some scientific reference value for the future research.